2004
DOI: 10.1111/j.1745-3992.2004.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

SAT Validity for Linguistic Minorities at the University of California, Santa Barbara

Abstract: The validity of the SAT as an admissions criterion for Latinos and Asian Americans who are not native English speakers was examined. The analyses, based on 1997 and 1998 UCSB freshmen, focused on the effectiveness of SAT scores and high school grade‐point average (HSGPA) in predicting college freshman grade‐point average (FGPA). When regression equations were estimated based on all students combined, some systematic prediction errors occurred. For language minorities, using only high school grades as a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Perhaps the absence of any differential prediction findings for Hispanics was attributable to not examining differential prediction by English language proficiency. Future research may extend the research of Zwick and Schlemer (2004) on the differential prediction of language minorities in multiple institutions to understand the extent to which HSGPA, SATM, and SATV differentially predict college grades for students with different levels of English proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the absence of any differential prediction findings for Hispanics was attributable to not examining differential prediction by English language proficiency. Future research may extend the research of Zwick and Schlemer (2004) on the differential prediction of language minorities in multiple institutions to understand the extent to which HSGPA, SATM, and SATV differentially predict college grades for students with different levels of English proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few researchers were interested in differential prediction (Abelson, 1952; Brown & Scott, 1967; Gulliksen & Wilks, 1950; Humphreys, 1952) and differential validity (Saunders, 1956; Stanley & Porter, 1967) prior to Cleary's classic study. After Cleary, the study of differential prediction grew in the late 1960s and 1970s (Bartlett & O’Leary, 1969; Bowers, 1970; Goldman & Hewitt, 1975, 1976; Goldman & Richards, 1974; Kallingal, 1971; Lefkowitz, 1972; Pfeifer & Sedlacek, 1971; Temp, 1971; Thomas & Stanley, 1969) and continues to receive serious attention (Norris, Oppler, Kuang, Day, & Adams, 2006; Sireci & Talento‐Miller, 2006; Young, 1990, 1991a, 1991b, 1994; Zwick, 2002; Zwick & Schlemer, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An aspect of the ethnic-group overprediction phenomenon that is less well known is that this overprediction tends to be more severe when HSGPA alone is used as a predictor than when HSGPA and SAT scores are used in conjunction (e.g., see Zwick & Schlemer, 2004). 2 A plausible hypothesis, investigated by Zwick and Himelfarb (2011), is that the overprediction of Latino and African American college grades occurs, at least in part, because these students are more likely than their White counterparts to attend high schools with fewer well-trained teachers and fewer instructional resources.…”
Section: Systematic Errors In Predicting Fgpamentioning
confidence: 99%
“…Certainly, additional research should identify other omitted variables that capture a portion of these observed group differences. For example, perhaps Blacks and Hispanics were less predictable given differential resources in their high school academic preparation (Adelman, 2006;Barton, 2003) and ESL students were less predictable due to differences associated with language proficiency (Zwick & Schlemer, 2004).…”
Section: Sigmentioning
confidence: 99%